Materials science and modern manufacturing : selected peer-reviewed full text papers from the 3rd International Scientific Conference of Alkafeel University (ISCKU 2021) : selected peer-reviewed papers from the 3rd International Scientific Conference of Alkafeel University (ISCKU 2021), March 22-23, 2021, Al-Najaf Al-Ashraf, Iraq - Al-Dahan, N.; Alosfur, Firas; Sopian, K. (Materials science forum ;, 2021)
Selected peer-reviewed full text papers from the 3rd International Scientific Conference of Alkafeel University (ISCKU 2021) Selected, peer-reviewed papers from the 3rd International Scientific Conference of Alkafeel University (ISCKU 2021), March 22-23, 2021, Al-Najaf Al-Ashraf, Iraq.